2012
DOI: 10.1371/journal.pone.0043733
|View full text |Cite
|
Sign up to set email alerts
|

Mtb-Specific CD27low CD4 T Cells as Markers of Lung Tissue Destruction during Pulmonary Tuberculosis in Humans

Abstract: BackgroundEffector CD4 T cells represent a key component of the host’s anti-tuberculosis immune defense. Successful differentiation and functioning of effector lymphocytes protects the host against severe M. tuberculosis (Mtb) infection. On the other hand, effector T cell differentiation depends on disease severity/activity, as T cell responses are driven by antigenic and inflammatory stimuli released during infection. Thus, tuberculosis (TB) progression and the degree of effector CD4 T cell differentiation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
6
50
1
1
Order By: Relevance
“…46 Interestingly, CD4 þ T-cells with a low CD27 surface expression have also been described as a marker of lung tissue destruction during pulmonary TB, suggesting its use as an immune assay to monitor the efficacy of TB therapy. 38 The studies on CD27 expression on Mtb-specific T-cells show similar and reproducible results, despite the differences of the experimental settings and clinical characteristics of the enrolled patients. 22,38e43,47 Therefore, the phenotype data of the CD4 þ T-cells are more consistent compared to the cytokine profile studies, suggesting that CD27 evaluation on Mtb specific-CD4 þ T-cells may be a useful tool for diagnosing TB stages.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…46 Interestingly, CD4 þ T-cells with a low CD27 surface expression have also been described as a marker of lung tissue destruction during pulmonary TB, suggesting its use as an immune assay to monitor the efficacy of TB therapy. 38 The studies on CD27 expression on Mtb-specific T-cells show similar and reproducible results, despite the differences of the experimental settings and clinical characteristics of the enrolled patients. 22,38e43,47 Therefore, the phenotype data of the CD4 þ T-cells are more consistent compared to the cytokine profile studies, suggesting that CD27 evaluation on Mtb specific-CD4 þ T-cells may be a useful tool for diagnosing TB stages.…”
Section: Introductionmentioning
confidence: 65%
“…53 Therefore, the decrease of CD27 expression on CD4 þ Tcells indicates the presence of highly differentiated effector T-cells that are able to produce cytokines. 38,44,45,54 TB is a chronic disease that leads to the increase of terminally differentiated T-cells. 14,22,43,55 In the present study, we show that one year after completion of TB therapy the level of CD27 expression increases in cured TB patients, indicating that the lack of a sustained inflammation leads the T-cells toward a less differentiated phenotype, probably with memory features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we found that the changes in HBHA-specific CD4 T cell frequencies were mirrored by changes in absolute numbers, which was not the case for the PPD-specific and the ESAT-6-and CFP-10-specific cells. Others have reported no differences in absolute numbers of Mycobacterium bovis BCG-spe- cific CD4 T cells in patients with TB infection versus healthy, skin test-positive controls (7) or of sonicated M. tuberculosis-specific CD4 T cells from actively infected individuals and M. tuberculosisexposed healthy controls (25). Why there is a difference in absolute numbers for HBHA stimulation but not with the other antigens is an interesting question, with the higher concentration of HBHA-specific CD4 T cells perhaps indicating that they are part of an ongoing systemic response in the latently infected population.…”
Section: Discussionmentioning
confidence: 98%
“…Этот показатель характеризует функциональную активность эф-фекторных Т-клеток и позволяет оценить тяжесть (активность) инфекционного процесса. Диффе-ренцировка T-лимфоцитов при ВИЧ-инфекции [9,17] и туберкулезе [12,16] как моноинфекций изучена достаточно подробно, в то время как ис-следования синергичного взаимодействие ВИЧ и туберкулеза на дифференцировку клеток не-многочисленны и нередко противоречивы.…”
Section: Introductionunclassified